[Dmt1]N/OFQ(1–13)‐NH2: a potent nociceptin/orphanin FQ and opioid receptor universal agonist. (18th December 2012) - Molinari, S; Camarda, V; Rizzi, A; Marzola, G; Salvadori, S; Marzola, E; Molinari, P; McDonald, J; Ko, MC; Lambert, DG; Calo', G; Guerrini, R
<x xml:space="preserve">Abstract</x> Background and Purpose Intrathecally (i.t.) administered nociceptin/orphanin FQ (N/OFQ) evokes antinociceptive effects in rodents. Recent studies in monkeys demonstrated that i.t. co‐application of N/OFQ and morphine elicits synergistic antinociceptive actions suggesting mixed N/OFQ peptide (NOP) and μ opioid receptor agonists as innovative spinal analgesics. Thus, novel N/OFQ related peptides were synthesized in order to identify and pharmacologically characterize a mixed NOP/ μ opioid receptor agonist. Experimental Approach The following in vitro assays were used: calcium mobilization in cells expressing the human NOP or classical opioid receptors and chimeric G proteins, receptor and [35S]‐GTPγS binding, [35S]‐GTPγS binding in rat spinal cord membranes, guinea pig ileum bioassay. In vivo experiments were performed in monkeys using the tail withdrawal assay. Key Results From calcium mobilization studies [Dmt1]N/OFQ(1–13)‐NH2 was selected as the most potent and least selective compound. The mixed NOP/opioid full agonist activity and high affinity of [Dmt1]N/OFQ(1–13)‐NH2 was confirmed at human recombinant receptors in receptor binding, calcium mobilization and/or [35S]‐GTPγS binding studies, at rat spinal cord receptors in [35S]‐GTPγS binding experiments, and at guinea pig receptors inhibiting neurogenic contractions in the ileum. In vivo in the tail withdrawal assay in monkeys i.t. [Dmt1]N/OFQ(1–13)‐NH2 was able to elicit robust and long‐lasting antinociceptive effects. Conclusions and Implications Collectively, these results demonstrate that [Dmt1]N/OFQ(1–13)‐NH2 behaves as NOP/opioid receptor universal agonist and substantiate the suggestion that such mixed ligands are worthy of development as innovative spinal analgesics.